EFFECT OF ADDING TWO LEVELS OF IRAQI SOLUBLE PROBIOTIC ON PERFORMANCE AND EGG QUILTY OF JAPANES QUAIL - Al- Tememy , Ammar T. (Diyala Agricultural Sciences Journal, 2013)
The aim of this study was to compare the effects of adding tow levels of Iraqi Soluble Probiotic (ISP) to the drinking water on performance of female Japanese quail take from State Board of Agriculture Poultry research station at Abu- Grab, sixty five female were used in this experiment with 40 days age. The birds were randomly distributed in to treatments (3replicated and 6 female each replicate) . The treatments : 1- T1 Tap were drinking water as follows: without addition (control) 2- T2 Tap drinking water+0.5gm of ISP each one litter water 3- T3 Tap drinking water+1gm of ISP each one litter water The result revealed that There were significant effects for the addition ISP to the drinking water on H.D % , eggs number, egg mass and feed conversation rate for T2 on T1&T3 in most experiment periods , however no significant effect for the these treatments on egg weight and egg quality. It can be recommend using bio-enhanced dissolved in water at a concentration of 0.5 g / liter of water for his contribution in improving the qualities of productivity and the quality of the egg recipes for female Japanese quail.